Analysis of Socialization Effectivity of Jamnapari Manure and Thickhead (Crassocephalum crepidioides) Leaf Utilization for Compost Production in Kalianyar Village, Bondowoso Regency - Munawar, Fahad Fauzan Al; Latif, Abdul; Ikhsan, Nurman Maulana; Chandra, Alicia Cherie; Masadi, Melody Angel; Maulana, Husaini; Fahrudin, Danil Eka; Afifah, Nur; Rahmawati, Irma; Vi Safrillah, M. Rizky Eka Putra (Journal of Agribusiness and Community Empowerment (JACE), 2023)
The optimization of Jamnapari manure in Kalianyar Village, Bondowoso Regency has not been considered to be optimal because of the lack of knowledge of farmers regarding its management. This becomes a problem itself as Jamnapari manure has a decent potential to be utilized as compost. Additionally, the thickhead plant is widely spread around Kalianyar Village, but it is also known as weeds by the villagers. The aim of this program is to analyze the effectiveness of the socialization of Jamnapari manure and thickhead utilization as the base materials of compost in Kalianyar Village, Ijen District, Bondowoso Regency. The respondents were chosen through a random sampling method and the t-test is used as the methodology in this research. After the results were proven to be significant, the measurement of socialization effectiveness (ES), which can be measured from the score pretest and post-test obtained by the farmers, was conducted with 11 respondents. Through used method, it was found that the obtained effectiveness value of 81.8% which gives evidence that this program was running very effectively due to the score increase on the post-test compared to the pretest’s score after the demonstration and socialization.